Implementasi Investasi Emas Syariah Perspektif Hukum Islam - Heradhyaksa, Bagas (Asosiasi Pengajar dan Peneliti Hukum Ekonomi Islam Indonesia (APPHEISI), 2022)
Investment is one of the economic activities which is managed by saving or investing funds in the form of money or assets in a company and these funds are managed by Investment Management, with the hope that the investment can be successful and will obtain profits and benefits in the future. In Indonesia, there are not only conventional investments but also sharia investments which are managed according to the principles of Islamic law, especially in Indonesia, the majority of the population is Muslim. One type of Islamic investment is in the form of gold investment. Gold can be used as a sharia-based investment instrument because apart from being safe, the price of gold is also relatively rising every year. With technological advances in this modern era, gold investment can be made through an online application which is of course registered with the Financial Services Authority. This article aims to find out the views of Islamic law on the implementation of sharia investments with gold instruments in online applications and about how to manage them. This article uses descriptive qualitative research methods to process data and produce a description of the data in the form of sentences that are arranged regularly and effectively and logically. The results in this study found that the Islamic view of the implementation of gold investment in online applications is allowed and in its management it is collected by the Investment Manager then the total successful funds will be invested into several instruments such as bonds, stocks, money markets or according to investment policies. The conclusion is that investing in gold in online applications is allowed because it is in accordance with Islamic principles and its management is safe. Therefore, the public, especially the millennial generation, can invest in gold in online applications.